THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF EIGHT GRADE STUDENTS IN SMPN 1 SUNGGUMINASA - Nurasmi Yuningsi; Mukhlisah Syahrul; Siti Nurmarwana; Muhammad Tahir; Suryadi Ishak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACT Vocabulary mastery plays a crucial role in students’ reading comprehension, particularly when understanding texts in narrative. Many students face difficulties in reading due to limited vocabulary knowledge. This research aims to investigate the correlation between vocabulary mastery and reading comprehension of the students, especially in narrative texts. This research used a quantitative correlational design involving 50 eighth-grade students at SMPN 1 Sungguminasa. The data were gathered through a test of mastery in vocabulary and a test of reading comprehension and analyzed using statistical analysis of correlation to determine the relation between the variables. The findings are expected to reveal a consequential correlation between vocabulary mastery and reading comprehension. This research results are anticipated to provide valuable insights for English teachers in developing effective strategies to enhance students’ vocabulary and improve their reading comprehension skills.